E-learning to m-learning: are the politeknik malaysia’s lecturers ready for the transition? - Ilya Binti Ismail; Noor Azlina binti Ahmad; Suriah binti Mohamad (Journal of Educational and Learning Studies, 2020)
The rapid development of 4IR in Malaysia has revolutionized the way of learning. Whole world is promoting electronic learning (e-Learning) as a new method to enhance the learning activities. The campaign continues to hike up when the world was shaken by the COVID19 pandemic, which caused most of the learning centre to close and force classes to be implemented completely online. Hence, this situation introduces the style of studying through mobile phone using the internet known as m-Learning. Although those two styles has been introduced for some time now at Politeknik Malaysia, there is no research conducted to measure the readiness of e-Learning and m-Learning within its context. As such, the aim of this study is to assess the lecturers' readiness in two politeknik namely; Politeknik A and Politeknik B. A total of 140 respondents were collected from using an online survey. A five-point Likert scale that demonstrated degrees of the agreement was applied to capture the lecturers' perceptions on their readiness for these two style learning. The results attained from this particular assessment can be used as some sort of guidelines for further development of e-Learning environment in Politeknik Malaysia.